Performance analysis of switched reluctance motor by using closed loop current control technique - Lokeshwar Reddy, Ch.; Satish Kumar, P.; Rao, J V G Rama; Sharanya, M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper presents the performance analysis of an 6/4 3-phase switched reluctance motor in terms of current, flux, torque and speed. When the speed of the motor is low the current rises quickly. If the speed is large the increase in current is low. In low-speed region, the current can be controlled by using chop/hysteresis current control mode. In this mode a voltage of +Vdc and -Vdc is apsimulation has been carried out for 6/4 3-phase switched reluctance motor using MATLAB/Simulink by applying closed loop current control technique. The detailed control of SRM for different speed modes has been carried out and the analysis of results demonstrated.